Risk Factors Leading to Anti-TNF Alpha Therapies in Pediatric Severe Uveitis - Osswald, Delphine; Rameau, Anne-Cécile; Terzic, Joëlle; Sordet, Christelle; Bourcier, Tristan; Sauer, Arnaud (Frontiers in Pediatrics, 2022)
Purpose: Pediatric uveitis is the leading cause of acquired child blindness, due to unremitting inflammation and long-term steroid exposition. Biotherapies with anti Tumor Necrosis Factor Alpha (TNFα) are effective in controlling inflammation for severe pediatric uveitis in recent studies. Major concern of Anti-TNFα prescription is the balance between the severity of the disease and side effects of the drug. The aim of the present study is to describe a cohort of children with severe uveitis and to highlight the risk factors for a pejorative development that led to the prescription of anti- TNFα drugs. Method: A retrospective case-control study was carried out on children with uveitis associated with systemic inflammatory disease or idiopathic uveitis, with a minimum follow-up of 5 years. Anti-TNFα-treated patients (Case) were studied and compared with patients who were not requiring anti-TNFα (Control). Univariate logistic regression analyses were performed to compare both groups and determine risk factors for Anti-TNFα therapy. Results: Seventy-five cases of pediatric uveitis were included, 14 cases and 61 controls. Risk factors associated with increased odds of anti-TNFα therapy were: Juvenile Idiopathic Arthritis (JIA) diagnosis (OR= 3.67[1.02-13.2], p=0.047), initial systemic disorder associated with uveitis (OR= 3.86[0.998-14.96], p=0.05), family history of autoimmune diseases (OR=6.37[1.76-23.1], p=0.005), uveitis diagnosis before the age of 6 years (OR= 3.49[1.08-11.3], p=0.036), ocular complications at the first stilt lamp exam (OR=18.01[1.04-313.4], p=0.047), low visual acuity at diagnosis (≥ 0.3 logMAR) (OR= 3.63[1.04-12.62], p=0.043) and especially low binocular acuity at diagnosis (≥ 0.3 logMAR) (OR= 5.48[1.43-20.95], p=0.013), and panuveitis (OR=8.68[2.42-31.17], p=0.0009), whereas in isolated anterior uveitis anti-TNFα treatment was rarely prescribed (OR=0.23[0.06-0.90], p=0.035). Conclusion Those risk factors could be used to establish a new follow-up and treatments schedule for severe uncontrolled uveitis. This could help to better predict the best time to start anti-TNF therapy. Key words: Uveitis – Pediatric – Anti TNFα – Risk Factors – Epidemiology – Inflammation.